2011
DOI: 10.1091/mbc.e10-08-0703
|View full text |Cite
|
Sign up to set email alerts
|

Novel function of keratins 5 and 14 in proliferation and differentiation of stratified epithelial cells

Abstract: Keratin expression in stratified epithelia is tightly regulated during squamous cell differentiation. Keratins 5 and 14 are expressed in mitotically active basal layer cells, but their function is not well defined. Reported here is the possible role of K14 in regulation of cell proliferation/differentiation in stratified epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
215
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(227 citation statements)
references
References 63 publications
11
215
1
Order By: Relevance
“…It was recently shown that the basal layer was less proliferative (Satoh et al, 2012a), and KRT5 expression may be associated with the suppression of cell proliferation in the basal layer. In mice, KRT5 is related to keratinocyte proliferation (Alam et al, 2011). The expression of KRT5 in higher vertebrates in a basal layer containing proliferative epidermal stem cells may apply to axolotl AEC.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that the basal layer was less proliferative (Satoh et al, 2012a), and KRT5 expression may be associated with the suppression of cell proliferation in the basal layer. In mice, KRT5 is related to keratinocyte proliferation (Alam et al, 2011). The expression of KRT5 in higher vertebrates in a basal layer containing proliferative epidermal stem cells may apply to axolotl AEC.…”
Section: Discussionmentioning
confidence: 99%
“…The keratin SC markers CK5 and CK14, which are important in maintaining epithelial proliferation (71), are highly expressed in SSCs. Keratin 15 a SC marker in the hair follicle (72), and keratin 17 could compensate for the loss of CK14 in mouse keratinocytes in maintaining cell growth (73).…”
Section: Sca1mentioning
confidence: 99%
“…Cytokeratin 5 (KRT5) is a filament protein that is expressed by epithelial cells and may play a role in maintaining the proliferative capacity of basally located epithelia [27]. We examined the expression of KRT5 in the fallopian tube stem-like cell fraction compared to differentiated FTE by immunostaining tissue sections of normal fallopian tube.…”
Section: Localization and Characterization Of Ftescsmentioning
confidence: 99%